SEGURANÇA PÚBLICA, MÍDIA E NEOCONSERVADORISMO: a naturalização da barbarização das relações sociais - Silene de Moraes Freire (Universidade Federal do Maranhão, 2019)
This article discusses the complexity of the barbarism of social relations in Brazil. Through the federal intervention in Rio de Janeiro in 2018, we indicate the centrality of the public safety policy, the media approach and the reorganization of the morality made by the evangelical movements in the consensus building needed for the consolidation of neoconservative hegemony – process that culminates in the results obtained in the elections of 2018. The consensus on the necessity for coercion appears as a nexus in the distinct speeches that permeated the intensification of the militarization of public security, expressed in the federal intervention in Rio de Janeiro, and of politics itself, establishing once and for all the social regression characteristic of late-capitalism.